Observations of Surface Acoustic Wave Strain and Resistive Strain Measurements on Broaching Tools for Process Monitoring - GERAGHTY, THOMAS; ALDWELL, BARRY (My University, 2014)
The monitoring of high end material removal processes continues to develop to greater levels of technical sophistication which in turn enable greater levels of insight into the process phenomena occurring at the tool-chip interface. The broaching process is a traditional machining process which is used extensively in the manufacture of some of the most expensive components of the aero engine. As a relatively slow cutting process with low degrees of freedom, broaching could be a target for strain based monitoring. It is well known that strain gauges provide a rich source of data when installed close to the cutting process. This research provides insight into the resistive strain gauge measurements during broaching. The paper also specifically focuses on the use of surface acoustic wave based strain measurement and provides some initial observations on the strain data available during tooth loading and cutting scenarios in broaching
PUBLISHED
Keywords: broaching tooth; strain field; monitoring